2010
DOI: 10.1037/a0018317
|View full text |Cite
|
Sign up to set email alerts
|

Pre-hurricane perceived social support protects against psychological distress: A longitudinal analysis of low-income mothers.

Abstract: Objective In this study, we examined the influence of pre-disaster perceived social support on post-disaster psychological distress among survivors of Hurricane Katrina. Method Participants (N = 386) were low-income mothers between 18 and 34 years of age at baseline (M = 26.4, SD = 4.43). The majority (84.8%) was African American; 10.4% identified as Caucasian, 3.2% identified as Hispanic, and 1.8% identified as other. Participants were enrolled in an educational intervention study in 2004 and 2005. Those wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
69
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 81 publications
10
69
2
1
Order By: Relevance
“…We found that decreased perceived social support from pre-to postdisaster reported previously remained significant at four-year postdisaster (Lowe et al, 2010), and that there was no change in perceived social support between the two postdisaster assessments. We also extended previous findings to show that the influence of predisaster perceived social support on four-year postdisaster GPD was mediated by exposure to fewer hurricane-related stressors (Lowe et al, 2010). Furthermore, we examined the impact of postdisaster perceived social support on longer-term mental health outcomes.…”
Section: Discussioncontrasting
confidence: 40%
See 3 more Smart Citations
“…We found that decreased perceived social support from pre-to postdisaster reported previously remained significant at four-year postdisaster (Lowe et al, 2010), and that there was no change in perceived social support between the two postdisaster assessments. We also extended previous findings to show that the influence of predisaster perceived social support on four-year postdisaster GPD was mediated by exposure to fewer hurricane-related stressors (Lowe et al, 2010). Furthermore, we examined the impact of postdisaster perceived social support on longer-term mental health outcomes.…”
Section: Discussioncontrasting
confidence: 40%
“…The purpose of this study was to extend the findings from Lowe et al (2010) by examining the association between both pre-and postdisaster perceived social support and longer-term psychological outcomes, specifically, GPD and PTS. We included the same sample but examined an additional wave of follow-up data, collected approximately four years after Hurricane Katrina.…”
Section: Current Studymentioning
confidence: 98%
See 2 more Smart Citations
“…Brouwers, Ever, and Tomic [29] developed the Teacher Interpersonal Self-Efficacy scale which consists of three subscales, namely Perceived Self-Efficacy in Classroom Management, Perceived Self-Efficacy in Eliciting Support from Colleagues, and Perceived Self-Efficacy in Eliciting Sarah et al, [19] studied that prehurricane perceived social support protects against psychological distress among low-income mothers. It indicates that predisaster social support can decrease both exposure to natural disasters and the negative psychological effects of natural disaster exposure.…”
Section: Social Support and Well-beingmentioning
confidence: 99%